VD_FINDINFO Arrêt / 2009 / 1045 vom 6. November 2009 - VD Tribunal cantonal (2009)
PRESTATION D'ASSURANCEAC, APTITUDE AU PLACEMENT | 15 al. 1 LACI, 16 LACI, 8 LACI, 56 LPGA, 57 LPGA, 58 LPGA, 59 LPGA, 60 LPGA, 61 let. a LPGA, 61 let. g LPGA, 117 al. 1 LPA-VD, 2 LPA-VD, 55 LPA-VD, 91 LPA-VD, 93 al. 1 let. a LPA-VD, 94 al. 1 let. a LPA-VD